In vitro antibacterial activity of SK&F 88070 against aerobic gram-positive and gram-negative cocci and Haemophilus influenzae. - Gooch, W M (1985)
The inhibitory activity of SK&F 88070, a cephalosporin whose kinetic characteristics in animals suggest the possibility of once-daily doses, was determined against 345 clinical isolates, and results were compared with the activities of ceftizoxime, ceftriaxone, moxalactam, methicillin, and ampicillin. The spectrum of SK&F 88070 is similar to that of ceftizoxime.